2012
DOI: 10.1001/archinternmed.2012.4508
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sex, Race/Ethnicity, and Educational Attainment on Human Immunodeficiency Virus Death Rates Among Adults, 1993-2007

Abstract: Background: Overall declines in human immunodeficiency virus (HIV) mortality may mask patterns for subgroups, and prior studies of disparities in mortality have used area-level vs individual-level socioeconomic status measures. The aim of this study was to examine temporal trends in HIV mortality by sex, race/ethnicity, and individual level of education (as a proxy for socioeconomic status).Methods: We examined HIV deaths among non-Hispanic white, non-Hispanic black, and Hispanic men and women aged 25 to 64 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 27 publications
(30 reference statements)
2
40
0
2
Order By: Relevance
“…Literature on this topic is scant, though one study reported that even after controlling for education (a proxy for SES), Black women still had higher HIV mortality rates than White men starting in 1999. [23] As reported in the present study, Black women have experienced the slowest decline in HIV mortality and understanding why this is the case should help us determine how to address the high rates among this group.…”
Section: Implications/future Researchmentioning
confidence: 56%
See 2 more Smart Citations
“…Literature on this topic is scant, though one study reported that even after controlling for education (a proxy for SES), Black women still had higher HIV mortality rates than White men starting in 1999. [23] As reported in the present study, Black women have experienced the slowest decline in HIV mortality and understanding why this is the case should help us determine how to address the high rates among this group.…”
Section: Implications/future Researchmentioning
confidence: 56%
“…Finally, the Black:White HIV mortality disparity resulted in 5603 excess Black deaths annually in the USA. These data demonstrate an indisputable White advantage with respect to HIV mortality, which has been occurring since at least 1990 [23,9,24,25,13].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…1,2 Blacks have the highest incidence of HIV infections, the highest prevalence of undiagnosed HIV and the greatest mortality among racial/ethnic groups. 3-5 They are least likely to be linked to and retained in care, to receive ART, and to achieve HIV RNA VS. 6,7 Latinos are disproportionately affected, as well. The annual incidence of HIV among Latinos is approximately three times that of Whites.…”
Section: Introductionmentioning
confidence: 99%
“…Para el año 2011, aquellos con mayor tasa de mortalidad por sida fueron Quindío con 15.56, Risaralda con 8.6 y Valle del Cauca con 7.9; en todos hay mayor mortalidad en hombres que en mujeres (20). En todo caso, lo que ha mostrado la literatura científica es que las desigualdades, bien sean geográficas, de género o socioeconómicas, se asocian con dificultades para el acceso a los tratamientos y la adherencia terapéutica, la aparición de comorbilidades y el mayor riesgo de mortalidad (21)(22)(23). Esto se agudiza cuando se trata de los grupos más desfavorecidos en la jerarquía social y en particular en población afrodescendiente (24).…”
Section: Introductionunclassified